Optimization of culture parameters for flavonoid production from callus and suspension cultures of the karas tree (Aquilaria malaccensis Lam.) - Daud, Nurul Hazwani (2013)
Plant tissue culture technique has been shown to be efficient for producing flavonoids at higher amount and lesser time period compared to intact plant. This study aimed at producing flavonoids in elevated amounts using callus and cell suspension cultures of A. malaccensis. Aquilaria trees not only produce secondary metabolites known as agarwood (gaharu) but also rich in flavonoids. To introduce plant materials into tissue culture, different sterilization regimes for leaf, nodes and seeds of A. malaccensis, were investigated. Pre-sterilization using 0.2% Benomyl for 15 minutes improved the number of „sterile and survived‟ individuals for all types of explants (83-90%), after surface sterilization using mercury chloride (0.1 to 0.2 % HgCl2). The most favorable explants for producing highest flavonoid cell lines were determined between leaf and nodal explants by using spectrophotometer and HPLC analysis. Result showed that flavonoid content in the leaf explants (8.85 ± 0.76 mg/g dry weight (DW)) was 7-fold higher than that of nodal explants (1.25 ± 0.53 mg/g DW). Leaf contained high amount of quercetin (16.19 ± 1.02 μg/g DW) then rutin (0.21 ± 0.31 μg/g DW). Nodes explants contained quercetin and rutin at 0.94 ± 0.07 μg/g DW and 0.06 ± 0.01 μg/g DW, respectively. Kaempherol was not detected in any of the explants. Leaf was used as explant for callus induction due to high flavonoid content and placed on different types of plant hormones to indicate the type of hormone use to induce callus. Callus grew best on Murashige and Skoog (MS) medium supplemented with 2.0 mg/L 2,4-dichlorophenoxy acetic acid (2,4-D) and 0.5 mg/L 6-benzylaminopurine (BAP). Total flavonoid content in MS medium supplemented with 2.0 mg/L BAP and 0.5 mg/L was 6- fold higher than in phytohormone- free MS medium. Using this optimal hormone combination, callus growth was observed on different strengths of MS medium, carbon sources and pH. Full-strength MS medium supplemented with 2.0 mg/L 2,4-D and 0.5 mg/L BAP, 20 g/L sucrose, in pH 5.7, significantly yielded the highest biomass (231 ± 0.13 mg DW /culture) of callus. These calli were used to initiate the cell suspension cultures. To enhance the flavonoid production in callus and cell suspension cultures, examine phenylalanine (Phe) was used as a precursor in ranged of 20 to 100 mg/L. Cell suspension culture added 60 mg/L Phe yielded the highest amount of total flavonoid (37.92 ± 0.77 mg/g DW), 4.8-fold higher than Phe-free cell culture, and 2-fold higher than that in calli (19.11 ± 0.36 mg/g DW). The suspension culture with 60 mg/L Phe had the highest amount of rutin (17.69 ± 1.37 μg/g DW), quercetin (3.46 ± 0.97 μg/g DW) and kaempherol (2.28 ± 1.67 μg/g DW). When compared the cell suspension culture with 60 mg/L Phe to Phe-free cell culture, only rutin and quercetin were detected and at lower levels, 1/10-fold and 1/4-fold, respectively. This study demonstrated that callus and cell suspension cultures of A. malaccensis produced flavonoids, and feeding the cultures with Phe elevated flavonoids levels and induced production of additional compound which is kaempherol.